Photobiomodulation Therapy for the Symptoms Related to Temporomandibular Joint Disk Displacement - Piotr A. Regulski; Kazimierz T. Szopinski; Špela Levičnik-Höfferle (Hindawi Limited, 2023)
Pain related to temporomandibular disorders (TMD) is a common problem that can significantly influence a patient's quality of life. Laser photobiomodulation (PBM) has been reported as a promising method in medicine for wound and bone healing, pain relief, and treatment of the temporomandibular joint (TMJ). Our clinical case aimed to demonstrate the effectivity of PBM using 1064 nm Nd:YAG laser for the treatment of pain and restricted mandible movement in a patient with anterior disk displacement of the left TMJ, using subjective (pain on visual analogue scale - VAS) and objective outcome measures [dynamic magnetic resonance imaging (MRI)]. PBM was performed on the left condyle in four sessions using a 1064 nm Nd:YAG laser with a flat-top handpiece. Results after 10 weeks showed an increase in mouth opening and a painless joint on palpation, with no reported adverse effects. An MRI of the TMJ confirmed the left disk displacement, however, with no signs of inflammation or effusion and with less pronounced disk deformity as compared with the first MRI examination. Use of PBM with Nd:YAG laser may be an efficient method for the management of orofacial pain in patients with acute and chronic TMJ disk displacements and may reduce the recovery time.